Alpha momentum and price momentum - Hannah Lea Hühn; Hendrik Scholz (International Journal of Financial Studies, 2018)
We analyze a novel alpha momentum strategy that invests in stocks based on three-factor alphas which we estimate using daily returns. The empirical analysis for the U.S. and for Europe shows that (i) past alpha has power in predicting the cross-section of stock returns; (ii) alpha momentum exhibits less dynamic factor exposures than price momentum and (iii) alpha momentum dominates price momentum only in the U.S. Connecting both strategies to behavioral explanations, alpha momentum is more related to an underreaction to firm-specific news while price momentum is primarily driven by price overshooting due to momentum trading.
Keywords: G11; G12; G14; 330; alpha momentum; price momentum; stock-specific return; price overshooting; slow information diffusion; reversal